Rapid Authentication of Medicinal Plants: Exploring the Applicability of Mass Spectrometry Imaging for Species Discrimination - Huang, Lieyan; Nie, Lixing; Wang, Xianrui; Wu, Yanpei; Dong, Jing; Kang, Shuai; Wei, Feng; Ma, Shuangcheng (Journal of the American Society for Mass Spectrometry, 2024)
In the past few years, mass spectrometry imaging (MSI) has brought many new inspirations to plant research. However, current MSI experiments usually include only a single batch of samples, casting doubts on the reproducibility of phytochemical distribution across different batches. Consequently, MSI has seldom been applied to conduct species discrimination. In this experiment, MSI was employed to discriminate between two taxonomically similar plants, Scutellaria baicalensis Georgi and Scutellaria rehderiana Diels. A new concept termed a “spatial marker” was proposed in this article, which referred to the phytochemical marker that presented both intraspecies similarity and interspecies dissimilarity. Multiple batches of S. baicalensis and S. rehderiana were analyzed using MSI, proving that the authentication protocol using spatial markers was reliable and reproducible. The observed spatial markers were further identified using on-tissue tandem mass spectrometry and liquid chromatography coupled with mass spectrometry. Additionally, the spectral data collected from MSI were utilized to set up algorithm models for species discrimination. External validation confirmed that the established random forest model was extrapolated well to unknown samples. Overall, this investigation successfully explored the analytical applicability of MSI, facilitating rapid authentication of medicinal plants.